Damage caused by Diceraeus (= Dichelops) melacanthus in maize plants subjected to combinations: bioinoculation and imidacloprid seed treatment - Ceolin Bortolotto, Orcial; Cruz Mendes, Marcelo; Teixeira Baixo, Bruna (Revista Ceres, 2023)
The aim of this study was to evaluate the damages caused by Diceraeus (=Dichelops) melacanthus in maize plants subjected to bioinoculation with or without imidacloprid seed treatment. In this study, five different combinations of bioinoculants and imidacloprid seed treatment were applied to maize seeds in a completely randomized design. The bioinoculants used were Azospirillum brasilense and Bradyrhizobium japonicum. From emergence, the plants were subjected to infestation with the stink bug D. melacanthus (one stink bug/plant), with permanence up to 21 days after emergence. After this period, the phytotechnical parameters (shoot and root) of the corn plants were evaluated. In general, plant height was higher when imidacloprid was applied, suggesting compatibility with bioinoculants. The chlorophyll a content was higher when bioinoculants were applied, regardless of whether imidacloprid was present. Finally, the results indicate that the bacteria A. brasilense and B. japonicum do not induce resistance to the level of D. melacanthus infestation used in the present study. Therefore, these bacteria can be used in combination with imidacloprid, allowing for greater plant height, higher chlorophyll a content, and reduced damage caused by D. melacanthus.